Ionothermal synthesis of metal aluminophosphates (IR) - Mazlina Musa (2013)
The aim of this thesis was to synthesise CoAPO-34 and FeAPO-34 using ionothermal synthesis in the presence of organic amines. Using this method provides an alternative route to prepare such materials under low pressure instead of the higher pressure associated with hydrothermal or solvothermal synthesis. Both materials have chabazite (CHA) topology and they are known to act as catalysts. CoAPO-34 was ionothermally prepared using 1-ethyl-3-methylimidazolium bromide (EMIMBr) in presence of 1, 6-hexadiamine (HDA). This study has found that when the synthesis was carried out without HDA, AIPO-11 was preferentially obtained instead of CoAPO-34. Broad line signals which appear between 2000 to 5000 ppm in both spin-echo 31 P NMR spectra of as-synthesised and calcined CoAPO-34 confirm that the C02+ ions have been successfully incorporated within the framework of the material. FeAPO-34 was synthesised under ionothermal conditions using 1-ethyl-3-methylimidazolium chloride in the presence of ethylenediamine (EDA). In the absence of EDA, the synthesis has produced AIPO-34 instead of FeAPO-34. Broad line signals that appear between 1000 to 14000 ppm in spin-echo 31p NMR spectra of both as-synthesised and calcined FeAPO-34 are direct evidence of isomorphous substitution of framework aluminum by Fe(lI) or Fe(III). Another aim of this study was to explore the ionothermal synthesis of copper containing aluminophoshate of DNL-1 (Cu/DNL-1). This material was attractive to explore because it contains 20 ring extra-large pores and Cu(l) species in the channels of the framework, potentially giving material the ability to simultaneous store NO and to generate NO from N02- anions. Cu/ONL-1 was successfully prepared under ionothermal conditions using EMIMBr and HOA. Without HOA in the synthesis, AIP0-11 was obtained. In this material, copper ions were not incorporated in the Cu/ONL-1 skeleton framework. This was confirmed by absence of broad line signal at >500 ppm in spin-echo 31p NMR spectrum of the sample. The copper ions are expected to be present as extra-framework cations. Extra-framework Cu(l) species that were formed by high temperature calcination of Cu/ONL-1 are active to produce NO from N02-. Therefore, the calcined Cu/ONL-1 can be used to simultaneously store and produce NO from nitrite. This has the potential to significantly extend the lifetime of gas delivery in the material to prevent thrombus formation.